2014
DOI: 10.3168/jds.2013-7189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AMP-activated protein kinase (AMPK) signaling and essential amino acids on mammalian target of rapamycin (mTOR) signaling and protein synthesis rates in mammary cells

Abstract: Regulation of mammary protein synthesis potentially changes the relationships between AA supply and milk protein output represented in current nutrient requirement models. Glucose and AA regulate muscle protein synthesis via cellular signaling pathways involving mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK). The objective of this study was to investigate the effects of essential AA (EAA) and acetate or glucose on mTOR and AMPK signaling pathways and milk protein synthesis rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 41 publications
1
73
1
4
Order By: Relevance
“…Acetate might have been a candidate to test the existence of feedback regulation because it is oxidized heavily in the mammary epithelium, but we have been unable to detect an effect of short-term, arterial acetate infusion on mammary ATP balance (Maas et al, 1995;Purdie et al, 2008). Similarly, glucose supplementation of mammary epithelial cells in vitro increased intracellular ATP concentrations, whereas acetate supplementation did not (Appuhamy et al, 2014).…”
Section: Mbf Is Locally Regulated By a Feedback Mechanismmentioning
confidence: 71%
“…Acetate might have been a candidate to test the existence of feedback regulation because it is oxidized heavily in the mammary epithelium, but we have been unable to detect an effect of short-term, arterial acetate infusion on mammary ATP balance (Maas et al, 1995;Purdie et al, 2008). Similarly, glucose supplementation of mammary epithelial cells in vitro increased intracellular ATP concentrations, whereas acetate supplementation did not (Appuhamy et al, 2014).…”
Section: Mbf Is Locally Regulated By a Feedback Mechanismmentioning
confidence: 71%
“…Menezes et al (2016) showed that reducing CP levels in diets of finishing cattle is possible without affecting animal performance besides to reduce N excretion to environment. Moreover, unbalanced diets represent economic losses, once protein is considered the most expensive nutrient in beef cattle diets (Appuhamy et al, 2014;Russel et al, 1992). Additionally, toxic effects related to N excess also lead to fertility impairment (Rhoads et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22). Mammalian target of rapamycin (mTOR), ribosomal protein S6 kinase (P70), ribosomal protein S6 (S6), factor 4E binding protein 1 (4EBP1), and eukaryotic translation initiation factor 4E (EIF4E) are key factors involved in the protein synthesis pathway (23)(24)(25)(26)(27). Furthermore, AMP-activated protein kinase (AMPK) plays a key role in regulating energy metabolism (28) and showed a negative association with selenium intake in rats (29).…”
Section: Introductionmentioning
confidence: 99%